Penerapan Metode RUP Untuk Sistem Pengajuan Cuti Pegawai Di SMA AZ-Zahra Palembang Berbasis Web Mobile - Iin Seprina; Evi Yulianingsih (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2022)
There are still a lot of even almost all types of companies that still use conventional methods in recording or calculating leave manually, one of them is SMA Az-zahra Palembang, Seeing with increasingly sophisticated technological advances, the author wants to help the problem of recording employee leave. Create a computerized leave application information system. The benefits include facilitating the recording process, both submitting leave for each employee and setting up leave confirmation so that each workforce can be properly distributed. The development is carried out using the RUP (Rational Unified Process) method and making designs using the Unified Modeling Language (UML) visual modeling. The application used in making this application is PHP, and MYSQL database. The hope of the information system created is that it can help accurately record employee leave and make the company better at managing its workforce.